The Concordance Database Manual - Haley, M. Alan (Apress, 2013)
The Concordance software has existed since 1984, originating as a project initiated by Dataflight Software to create a powerful full-text information retrieval system that could be deployed on personal computers. Now, more than 20 years later, Concordance is widely recognized as one of the most useful and fundamental litigation support software packages available.